STRATEGI INTERNALISASI NILAI MODERASI BERAGAMA DALAM MEMBENTUK KARAKTER NASIONALIS SISWA: strategies for internalizing religious moderation in shaping students' nationalist character - Ahmad Fauzi; Jazilur Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article aims to describe and analyze in depth the strategies for internalizing religious moderation in shaping students' nationalist character. This research employs a qualitative approach with a case study design. The study was conducted at MTs. Raudlatul Hasaniyah Mojolegi Gading from January to May 2025. Data collection techniques included interviews, observation, and documentation. Data analysis followed the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results of this study indicate that the strategies for internalizing religious moderation in shaping students' nationalist character at MTs. Raudlatul Hasaniyah Mojolegi Gading include the integration of religious moderation values in Aswaja and Civics (PPKN) lessons, religious moderation seminars on national and civic life, the commemoration of Independence Day and National Santri Day (HSN), the exemplary role modeling of moderate-nationalist teachers, and participation in flag ceremony activities.